Avaliação experimental de correlações empíricas para correção da superestimação das leituras em medidores tipo cone em escoamento bifásico - Correia, Wesley Joaquim Henrique (2016)
The work seeks to experimentally evaluate the empirical correlations for correction ofthe over-reading in measurements of wet gas-flow in cone devices. The purpose is basedon the technological challenges of natural-gas flow measuring in wet-gas condition. Bya literature search, the current state of the wet-gas flow measuring technology, how thesystem of measurement works, the pros and cons, and a discussion on the standardizationand regulations related to the subject were presented. In the experimental part it waspresented the aspects os the flow patterns and their influence on the over-reading, behavioranalysis of the cone device, evaluation of the parameters that affects the wet-gas measuring.Also it is compared the efficiency of existent correlations applied to the data of the presentwork. The cone device is seen as an important measurement device before the presentscenario. To know its behaviour when using the existent correlations is important, oncethere is no general correlation for correction